PHARMACOPHORE SCREENING AND MOLECULAR DOCKING OF PHYTOCONSTITUENTS IN POLYGONUM SAGITTATUM FOR CYCLOOXYGENASE-2 INHIBITORS DISCOVERY. - Megantara, Sandra; Mw, Agung Yodha; I, Sahidin; Diantini, Ajeng; Levita, Jutti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to discover cyclooxygenase (COX-2) inhibitors from Polygonum sagittatum (Polygonaceae), by screening the pharmacophores based on the interaction of mefenamic acid with COX-2, followed by molecular docking with COX-2. Methods: The protein crystal structure of human COX-2 in complex with mefenamic acid (PDB code: 5IKR) was selected, its ligand-protein interaction was studied by employing LigandScout to obtain the pharmacophore features. The features were validated against PGH2 database provided at http://dude.docking.org/targets/pgh2, and the result was used to screen the pharmacophores of the phytoconstituents isolated from P. sagittatum. Furthermore, a molecular docking of the phytoconstituents into COX-2 binding pocket was performed. The compounds were generated using MarvinSketch, and the energy was optimized by employing LigandScout MMFF94. Celecoxib and mefenamic acid, selective COX-2 inhibitors, were used as the standard drugs. Results: The pharmacophore features obtained were aromatic ring (hydrophobicity) and two hydrogen bond acceptors, which are proved valid against PGH2 training set (GH score = 0.78; AUC100% receiver operating characteristic curve = 0.97). There are four phytoconstituents (quercetin, protocatechuic acid, vanicoside A, and vanicoside B) that fit the features, and therefore, are predicted to be active in inhibiting COX-2. The docking reveals that three phytoconstituents (methyl-4-hydroxycinnamate, quercetin, and methyl gallate) interact with Tyr385, an important amino acid residue in COX-2 binding pocket. Quercetin is the best in inhibiting the enzyme (docking score −8.60 kcal/mol; inhibition constant 0.5 μM), compared to mefenamic acid (docking score −8.90 kcal/mol; inhibition constant 0.3 μM) and celecoxib (docking score −10.00 kcal/mol; inhibition constant 0.05 μM). Conclusions: Phytoconstituents in P. sagittatum fit the pharmacophore features generated from mefenamic acid and COX-2 complex; therefore, they might be potential in inhibiting COX-2 enzyme. Their binding modes are more similar to that of mefenamic acid than of celecoxib. Of those, quercetin is the best in inhibiting the enzyme. Its inhibitory activity is equal to mefenamic acid but is weaker than celecoxib.